The Decision to Postpone Marriage among the Sandwich Generation: A Maqashid Shari'ah Review - Izzati, Nurul; Darmawan, Aldy (Jurnal AL-AHKAM, 2024)
This study aims to analyze the Maqashid Shari'ah review of the decision to delay marriage in the sandwich generation, which is based on rational considerations such as concerns about financial responsibility and the potential to form the next sandwich generation while they are of marriageable age. The literature review method was used with thematic analysis helping to identify and interpret the findings. The conclusions of this study show that concerns about financial hardship and fairness towards spouses are the main factors driving the decision to postpone marriage for the sandwich generation. Marriage in Islam is not a decision that should be forced on everyone without consideration, but must be based on readiness and ability both in terms of economic and mental readiness. Postponing marriage because it has already become a sandwich generation in order to break the chain of sandwich generation is a wise action to ensure that when marriage occurs, the individual is better prepared and able to carry out the role in family life in accordance with Islamic law in accordance with maqashid sharia.